2022
DOI: 10.1101/2022.06.21.496830
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Drug-induced adaptation along a resistance continuum in cancer cells

Abstract: Advancements in rational drug design over the past decades have consistently produced new cancer therapies, but such treatments are inevitably countered through an adaptive process that fosters therapy resistance. Malignant cells achieve drug resistance through intrinsic and acquired mechanisms, rooted in genetic and non-genetic determinants. In particular, recent work has highlighted the role of intrinsic cellular heterogeneity in the emergence of transient drug-tolerant persister cells that survive drug trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 95 publications
1
11
0
Order By: Relevance
“…In all three treatments, we found that prolonged treatment resulted in significant changes in pathway activity, most of which have been reported in the literature to be involved with treatment resistance or aggressive cancer phenotypes [34][35][36][37][38][39][40][41] . Thus, across all three different treatments, we found further evidence that the transcriptional states of the population change dynamically as a function of the duration of treatment 27 .…”
Section: Prolonged Treatment With the Same Agent Causes Population-le...supporting
confidence: 61%
See 2 more Smart Citations
“…In all three treatments, we found that prolonged treatment resulted in significant changes in pathway activity, most of which have been reported in the literature to be involved with treatment resistance or aggressive cancer phenotypes [34][35][36][37][38][39][40][41] . Thus, across all three different treatments, we found further evidence that the transcriptional states of the population change dynamically as a function of the duration of treatment 27 .…”
Section: Prolonged Treatment With the Same Agent Causes Population-le...supporting
confidence: 61%
“…Our findings further support a growing body of evidence that resistance to treatment can not be explained by single mechanisms acting in isolation 10,49 . Rather, resistance reflects a complex and dynamical process in which diverse and continuously evolving cellular states are generated 9,27 . Our work contributes another layer of phenotypic complexity by demonstrating that the diverse clones generated under treatment have differential sensitivities to subsequent treatments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…S6E). In summary, our results suggest that similar to the multifactorial nature of cell-intrinsic resistance mechanisms 14,15 , EMDR cannot be reduced to a single molecular pathway. Instead, it integrates the functional impact of multiple mechanisms enabling tumor cells to escape therapeutic elimination within peristromal niches and contributing to tumor growth relapse (Fig.…”
Section: Suppression Of Individual Mechanisms Of Emdr Enhances In Viv...mentioning
confidence: 74%
“…Cell-intrinsic non-genetic differences can either be pre-existing within a population or can be induced by the selective pressures (e.g., anti-cancer therapies). 6 , 7 , 8 , 25 , 26 , 27 , 28 These modes are not necessarily mutually exclusive and are often attributed to phenotypic plasticity, such as the well-established paradigm of epithelial-mesenchymal transition. 29 Collectively, genetic and non-genetic variabilities can impart fitness advantage to a cell, enhancing its survival, proliferation, and dominance over other cells in both pre-malignant lesions and cancerous tissues.…”
Section: Clonality As a Cancer Cell-intrinsic Propertymentioning
confidence: 99%